The Effect of Spiritual Intelligence, Transformational Leadership Style, and Emotional Intelligence on Village Government Officials Performance in the Villages of Nagerawe and Focolodo Rawe – Boawae Sub-District – Nagekeo Regency – East Nusa Tenggara Province - Poma, Sarlianus (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
The purpose of this study is to determine and find out The Effect of Spiritual Intelligence Variable, Transformational Leadership Style Variable, and Emotional Intelligence Variable on Village Government Officials Performance Variable in the Villages of Nagerawe and Focolodo Rawe Boawae Sub-District – Nagekeo Regency – East Nusa Tenggara Province. This study used a quantitative method with the type of survey research; the research instrument used in this study was a questionnaire. The number of samples in this study was 54 respondents. The sampling technique used in this study was the purposive sampling method. The research data were analyzed by using the statistical package for the social science (SPSS) software Version 25. The results of this study proved that (1) in the Spiritual Intelligence Variable (X1) the Value of Significance was 0.027 ≤ 0.05 and the value of tcount was 2.839 ≥ the value of ttable 2.008, this proved that the Spiritual Intelligence Variable (X1) had a significant effect on the Performance Variable (Y). (2) Transformational Leadership Style Variable (X2) the Value of significance was 0.137 ≥ 0.05 and the value of tcount was 1.513 ≤ the value of ttable 2.008, this proved that Transformational Leadership Style Variable (X2) had no significant effect on the Performance Variable (Y). (3) Emotional Intelligence Variable (X3) the value of significance was 0.035 ≤ 0.05 and the value of tcount was 2.203 ≥ the value of ttable 2.008, this also proved that Emotional Intelligence Variable (X3) had a significant effect on the Performance Variable (Y). Meanwhile, for the result of the F-test (simultaneous) the value of significance was 0.000 ≤ 0.05 and the value of Fcount was 30.292 ≥ the value of Ftable 2.790, so it can be concluded that there was an effect of the Spiritual Intelligence Variable (X1), Transformational Leadership Style Variable (X2) and Emotional Intelligence Variable (X3) simultaneously on Performance Variable (Y). The result of the coefficient of determination (R2) test showed that the value of the coefficient of determination (adjusted R square) was 0.624. This means that 62.4% of the Performance Variable (Y) in this study was affected by Spiritual Intelligence Variable (X1), Transformational Leadership Style Variable (X2), and Emotional Intelligence Variable (X3), while the rest 37.6% of the Performance Variable (Y) was affected by other variables which were not examined in this study. Keywords: Spiritual Intelligence, Transformational Leadership Style, Emotional Intelligence, and Performance.